TRADISI ABDA’U DI DESA TULEHU KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH ABAD XX - Sumarni Lausiry Lausiry; La Ode Ali Basri (Jurusan Ilmu Sejarah Fakultas Ilmu Budaya Universitas Halu Oleo, 2019)
This research aims to describe the Abda'u Tradition at Tulehu Village, Salahutu District, and Central Maluku Regency. The method used in this study was the historical method according toKuntowijoyo with the following stages: 1) Topic selection, 2) Collection of sources, 3) Verification,4) Interpretation, and 5) Historiography. The theory used was the theory of rationality. The resultsof the study showed that: 1) The tradition of abda'u in Tulehu Village was one of the traditions ofthe local community which was believed to have a positive impact and also united the kinshipamong people and brough prosperity. This tradition must be carried out every year as a sense ofdevotion as a servant of Allah. 2) The process of carrying out the abda'u tradition at Tulehu Villageconsisted of a procession of slaughtering livestock sacrifices. General slaughter was carried outafter the Eid al-Adha prayer and specifically slaughter was carried out in the afternoon with threecompanion goats (one core and two companions). 3) Values embodied in the implementation of thistradition were social values, religious values, cultural values and educational values. Keywords: Tradition; Abda'u, Tulehu; Maluku.